All about the Rites From Canonised Ritual to Ritualised Society - Cheng, Anne; Feuillas, Stéphane (Institut des civilisations, 2023)
This third volume of the "Myriades d'Asies" series is the result of an international conference which was held at the Collège de France in 2018, and published in book form by Hémisphères Editions in 2021, the present digital edition being a revised and improved version of the printed edition. It intends to look afresh at the way ancient China progressively evolved into a ritualistic society, that is a world in which social interactions in times of peace were to be conceived of within the category of rites. If such a category remains difficult to define univocally, it has appeared to us that one possible approach was to study the canonization in the Han period of a compendium of texts which aim at regulating conducts, be it social behaviour, body language, speech, the relations between the living and the dead, as well as power relations and the agenda of human activities. We are talking more specifically about a cluster of three texts which soon came to acquire the status of "classics" and which are now known as the Ceremonial and Rites (Yili 儀禮), the Rites of Zhou (Zhouli 周禮), and the Book of Rites (Liji 禮記). The first objective of the volume is to examine the articulations between these texts and more precisely to inquire about the patterns of, and motivations for, the canonization of ritual in the first century of Han rule, about the rewriting effects, and about the incorporation of very heterogeneous texts in the establishment of the canon. This primary approach to "the world of ritual" is followed by a more specific study of the most composite text of the compendium, the Book of Rites. How did the ancient commentaries of this text contribute to model the interpretation of rites, and in what way did the classic never cease to be an open text, going through successive phases of deconstruction, desacralisation or reconstruction that allowed for the ritual order to be constantly recomposed as dynasties went by? And how did the text relate to ancient Chinese ritual practices revealed by archeological discoveries or by different sources? The final sections attempt to show, by contrast with other traditions and sociological approaches, how the canonization of ritual in China has shaped the sense of rites and the forms of social and political inquiry in ancient China, and how ritual still serves to underpin some modern thinking about the organization and management of men. Brought in the light of other conceptions elaborated in Asian or European societies, the ritual that has developed in China out of the Han canon thus appears to be an alternatively critical or ideological basis for a variety of discourses on the art of handling human affairs.